Implementation of Financial Technology (Fintech) in the Collection of Zakat, Infak, and Sedekah Among Generation Y and Z (Case Study: BAZNAS RI) - Kurniawati, Neneng Nadila; Hidayat, Muhammad Rohmat (International Journal of Zakat, 2025)
This research is based on the author's interest in the development of financial technology or fintech adapted by Zakat, Infak, and Sedekah (ZIS) institutions in their collection mechanisms. Then, in relation to the subject of this research, it is aimed at the millennial generation or Gen Y and Gen Z as parties considered adaptive to the times, especially in the field of technology. Thus, the research preparation implements a qualitative method with a literature review approach. This research is presented descriptively with secondary data sources obtained from relevant sources. The results of this study illustrate that fintech is beneficial for muzakki in providing an easy and efficient mechanism for zakat collection. BAZNAS is committed to facilitating zakat payers with digital or fintech payments through e-commerce by providing services that make it easier for the community to fulfill their obligations of zakat, infak, and sedekah through a server-based system with PayTren. Fintech has proven to have a positive impact because it simplifies transactions and can be accessed anywhere. However, there is a generation that is still not confident about account security and there are still concerns about the potential leakage of personal data.